KOORDINASI PELAKSANAAN JOB EXPO OLEH DINAS TENAGA KERJA KOTA PEKANBARU - Nila sari; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Job market or often known as job expo is an annual event organized by the City Workforce Pekanbaru with the aim to reduce unemployment in the City Pekanbaru. In the implementation of this job expo the City Workforce Pekanbaru cooperating with the company in the City Pekanbaru. In the implementation job expo is still low placement of workers absorbed, the number of job vacancies ar little considering the number of job seekers are increasing, then the law number 13 0f 2003 on employment to give authority to the company as a provider of job vacancies provided by the company in the activity of job expo.The method used in this study is purposive sampling, the data source used in this study is covering primary data and secondary data, the location of research conducted on the Labor and Transmigration office of Pekanbaru City. Informant of this research head of placement of employment, head of section of employment of domestic worker, PT. Swakarya Mandiri, PT. Inter Boga Nusantara and job seekers.The concept of theory used by research is the theory of coordination according to sugandha wich consist of : organizational structure, planning, procedures and supervision. This research use qualitative descriptive data assessment, data collection techniques used are observation, interview and documentation. To ensure the validity of research data using data source tringulation.From the results of the research, it is known that the coordination of job expo implementation by City Workforce Pekanbaru not implemented well, because the low labor absorbed in the placement and available job vacancies are still small. As for the factors that hinder the coordination of job expo implementation by the Workforce Pekanbaru namely: budget, communication/ information and job vacancy.Key Words: Coordination, Implementation and Job Expo